Knockout mutation in TaD27 enhances number of productive tillers in hexaploid wheat - Awan, Muhammad Jawad Akbar; Amin, Imran; Rasheed, Awais; Saeed, Nasir A.; Mansoor, Shahid (Frontiers in Genome Editing, 2024)
Recent advances allow the deployment of cluster regularly interspaced short palindromic repeats (CRISPR)-associated endonucleases (Cas) system for the targeted mutagenesis in the genome with accuracy and precision for trait improvement in crops. CRISPR-Cas systems have been extensively utilized to induce knockout or frameshift mutations in the targeted sequence of mostly negative regulating genes for wheat improvement. However, most of the reported work has been done in noncommercial varieties of wheat and introgression of edited alleles into breeding population comes with the penalty of unwanted linkage-drag. Wheat yield is controlled by various genes such as positive and negative regulators. The TaD27 gene is described as a negative regulator of shoot branching or tillering and involved in the biosynthesis of strigolactones. In this study, we developed Tad27 knockout mutant lines of an elite wheat cultivar that showed a twofold increase in the number of tillers and 1.8-fold increase in the number of grains per plant. Subsequently, enhancing the grain yield without any morphological penalty in the architecture of the plants. The co-transformation of regeneration enhancing growth regulator, Growth Regulating Factor 4 (GRF4) and its cofactor GRF-Interacting Factor 1 (GIF1), under single T-DNA cassette improved the regeneration efficiency up to 6% of transgenic events from mature embryos of wheat. Our results indicate that the CRISPR-mediated targeted mutagenesis confers the potential to knockout yield-related negative regulators in elite cultivars of wheat that can substantially enhance grain yield per plant and this strategy can be harnessed for the improvement of future wheat.